Infertile couples still undergo assisted reproductive treatments without initial andrological evaluation in the real‐life setting: A failure to adhere to guidelines?. (22nd September 2021) - Pozzi, Edoardo; Boeri, Luca; Candela, Luigi; Capogrosso, Paolo; Cazzaniga, Walter; Fallara, Giuseppe; Cignoli, Daniele; Belladelli, Federico; Cornelius, Julian; Abbate, Costantino; Papaleo, Enrico; Viganò, Paola; et al.
Abstract: Background: The EAU guidelines on male sexual and reproductive health state that both partners of the infertile couple should undergo simultaneous investigation. Objectives: To assess the prevalence and the characteristics of infertile men who were referred for an andrological evaluation after failed attempts of Assisted Reproductive Technology (ART) with those who were evaluated at the beginning of their infertility pathway at a single academic centre over a 17‐year period. Materials and methods: Data of 3213 primary infertile couples assessed between 2003 and 2020 were analysed. Descriptive statistics compared the overall characteristics of male partners of couples with (+ART) or without (–ART) previous ART prior to andrological consultation. Logistic regression models analysed variables associated with +ART. Local polynomial regression models explored the probability of +ART over the analysed time frame. Results: Of all, 493 (15.3%) participants were +ART. Patients and female partners' age was higher in +ART couples (all p ≤ 0.04). Sperm concentration, progressive sperm motility and normal sperm morphology were lower in +ART than in –ART patients (all p < 0.001), along with a greater percentage of non‐obstructive azoospermia in +ART compared to –ART men ( p < 0.0001). At univariable analysis, patient age and partner age >35 years and a less recent assessment were associated with +ART status (all p ≤ 0.04). Male age and less recent years of assessment were also independent predictors of +ART, after accounting for partner's age >35 years (all p < 0.01). A not significant decrease of this pattern was observed throughout the last 7 years at local polynomial regression models. Discussion: Overall awareness towards the importance of a comprehensive evaluation for the male partner of every infertile couple should therefore be further strengthened. Conclusions: Approximately 15% of couples still undergo ART without any initial andrological evaluation in the real‐life setting. A not significant decrease in this trend was observed over most recent years.